Pengaruh PHR dan Jumlah Penduduk terhadap PAD serta Pertumbuhan Ekonomi di Provinsi Bali - Tesyaningrum, Made Dylla; Bendesa, I K. G. (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
The purpose of this study was to analyze the effect of tax on hotel and restaurant (PHR), population and revenue (PAD) on economic growth at the Regency / City in the province of Bali. This research was conducted at the Regency / City in the province of Bali. Data collected through the documents contained in the Central Bureau of Statistics of Bali Province. The analytical method used path analysis. The analysis showed that the PHR have positive effect direct on the PAD, while the number of the population has no effect on PAD. In the next test, PHR variables, population and PAD have a positive and direct effect on Economic Growth in Regency / City in the province of Bali. Variable PAD is an intervening variable and indirect positive influence PHR and the number of people on the Growth PHR Ekonomi.Pengaruh indirectly to economic growth through the revenue of 0035, means that the PHR indirect effect on growth by PAD is at 3.5 percent. The value of the indirect effect of population on the amount of economic growth through the revenue of 0007, means that the indirect effect of a population to economic growth through revenue by 0.7 percent.
Keywords: pajak hotel dan restoran; jumlah penduduk; pendapatan asli daerah; pertumbuhan ekonomi